The impact of collaborative model assisted by Google Classroom to improve students’ creative thinking skills - Jumadi Jumadi; Riki Perdana; Muhammad Helmi Hariadi; Warsono Warsono; Andi Wahyudi (Institute of Advanced Engineering and Science, 2021)
Indonesian students' creative thinking skill is still at a low level. This study aimed to examine the effectiveness of project collaborative model assisted by Google Classroom (PjCM-GC) in improving students' creative thinking skills. This research explored the differences between students who learned through the demonstration model (DM), project collaborative model (PjCM), and project collaborative model assisted by Google Classroom (PjCM-GC). It was a quasi-experimental with pre and post-test design. The population of this research was students at Senior High School, Lombok Timur-Indonesia. Random sampling technique was employed in this study. The sample was 86 science students grade XI (15-16 ages) who studied in SMAN 1 Aikmel. The data analyzed by paired-sample t-test, comparative-descriptive analysis, and ANOVA mixed design using SPSS 24. The study showed that The PjCM-GC group had a significant difference in the level of creative thinking skills (sig .0000). The PjCM-GC was the most effective model to improve the skills with a gain score of .47 (medium). Learning with the PjCM-GC model can be an alternative for policymakers and teachers to solve the problems of creative thinking.